SKIN TOXICITIES AND ALLERGIC REACTIONS ASSOCIATED WITH BOTULIN TOXIN INJECTION FOR AESTHETIC PROCEDURES - Dr Iqra Jamshaid; Dr Palwasha Ishaque; Dr Amber Shami; Dr Nishwah Khan; Dr Sana Usman; Dr Sara Gull (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Cosmetic surgery procedures have increased manifolds all over the world owing to the ever-increasing demand of people to look beautiful and young. Injectable treatments like botulinum toxin are becoming more popular owing to their rapid, well-defined, and lasting results for the reduction of facial fine lines, wrinkles, and facial rejuvenation. Objectives: The main objective of the study is to find the skin toxicities and allergic reactions associated with botulin toxin injection for aesthetic procedures. Methodology: This observational study was conducted at Karachi with the collaboration of different aesthetic clinics in Islamabad during June 2023 to June 2024. No interventions or modifications were made to the standard clinical practices followed by the healthcare providers administering the injections. Patients who opted for botulinum toxin injections for aesthetic purposes such as wrinkle reduction or facial rejuvenation were included in the study. Results: Data were collected from 55 patients with a majority being female (76%) and the largest age group being 31-40 years (36%). Skin reactions occurred in 11% of patients, with redness being the most common reaction (5.5%), followed by swelling (3.5%) and itching (2%). Conclusion: It is concluded that botulinum toxin injections for aesthetic purposes have a generally favourable safety profile, with mild and transient skin toxicities and allergic reactions occurring in a small percentage of patients.